2012
DOI: 10.7475/kjan.2012.24.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive Rehabilitation Program on Cognitive Function, Depression, and Activities of Daily Living among Patients with Strokes

Abstract: Purpose:The purpose of this study was to test the effectiveness of a cognitive rehabilitation program for the patients having an acute stroke. The variables evaluated were cognitive function, depression and activities of daily living (ADLs). Methods: A non-equivalent control group pretest-posttest design with sixty-two subjects from two separated institutions was the design for the study. Thirty-three patients were assigned to the treatment group and 29 patients comprised the comparison group. The treatment gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…As a result of this study, the subjects who participated in the cognitive rehabilitation program improved their cognitive function scores by more than 3 points after the intervention, from 20.00±4.53 points to 23.25±4.43 points. The score was 1.98, which was similar to the result reported that it improved to 5.18±1.40 points [42]. Another previous study showed similar results to this study, from 15.20±4.83 points to 18.00±5.67 points [5].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As a result of this study, the subjects who participated in the cognitive rehabilitation program improved their cognitive function scores by more than 3 points after the intervention, from 20.00±4.53 points to 23.25±4.43 points. The score was 1.98, which was similar to the result reported that it improved to 5.18±1.40 points [42]. Another previous study showed similar results to this study, from 15.20±4.83 points to 18.00±5.67 points [5].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, there have been many studies that applied cognitive rehabilitation programs to stroke patients [5,42], but it is judged that studies that comprehensively deal with the effects on cognitive function, depression, and sleep are still insufficient. In addition, many cognitive rehabilitation programs used in other studies applied only cognitive and emotional activities excluding physical activities.…”
mentioning
confidence: 99%
“…Furthermore, in patients with PASC, cognitive impairment may drive symptoms of depression regardless of whether patients were hospitalized for their COVID-19 infection. Prior research suggests the promise of cognitive rehabilitation for improving depression ( Jang & Jun 2012 ). Thus, it may be advantageous to offer both cognitive rehabilitation and evidence-based treatments for depression to patients with PASC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that using CoTras for training improves cognitive function in children with developmental disabilities [ 13 ] and can be used as an effective training program to improve cognitive function in adults with dementia [ 14 ]. Additionally, it has been proven effective in improving memory in healthy elderly people [ 15 ] and cognitive function in patients with impaired cognition, such as patients with cerebrovascular accidents [ 16 , 17 ] and traumatic brain injury [ 18 ]. CoTras is widely used in geriatric and pediatric centers and hospitals in Korea for cognitive rehabilitation.…”
Section: Introductionmentioning
confidence: 99%